Association of polymorphism genes LPL, ADRB2, AGT and AGTR1 with risk of hyperinsulinism and insulin resistance in the Kazakh population - Shakhanova, Aizhan; Aukenov, Nurlan; Nurtazina, Alma; Massabayeva, Meruyert; Babenko, Dmitriy; Adiyeva, Madina; Shaimardonov, Nurlan (Biomedical reports, 2020)
Hyperinsulinism and insulin resistance are closely associated with several common diseases including type 2 of diabetes, cardiovascular diseases, and metabolic syndrome. The present study aimed to determine the association between hyperinsulinism, insulin resistance and the polymorphism of genes, including angiotensin II receptor type 1 (AGTR1), angiotensinogen (AGT), [beta]2-adrenoreceptor (ADRB2) and lipoprotein lipase (LPL), in the Kazakh population. The design of the current research was a case-control study, involving 460 subjects (age range, 18-65 years). For every subject, plasma glucose, insulin, total cholesterol, triglycerides, high-density lipoprotein, low-density lipoprotein, apolipoprotein B and apolipoprotein A1 were examined. Moreover, reverse transcription-quantitative PCR was conducted to detect the polymorphism genes LPL Ser447Ter, ADRB2 Gln27Glu, AGT Thr174Met and AGTR1 A1166C. Hyperinsulinism was considered when the insulin level was elevated >24.9 IU/ml. The homeostasis model assessment insulin resistance (HOMA-IR) was used to evaluate insulin resistance. The subjects were divided into hyperinsulinism (17 men and 24 women) and normal level insulin (214 men and 205 women) groups, which were also split into insulin resistance group (HOMA-IR >2.7; 80 men and 105 women) and those without insulin resistance group (151 men and 124 women). The results suggested that LPL Ser447Ter (rs328) allele G was associated with a lower risk of hyperinsulinism (P=0.037). Furthermore, polymorphisms of genes ADRB2 Gln27Glu (rs1042714), AGT Thr174Met (rs4762) and AGTR1A1166C (rs5186) were not associated with hyperinsulinism and insulin resistance in the Kazakh population. No interaction was identified between LPL Ser447Ter, ADRB2 Gln27Glu, AGT Thr174Met and AGTR1 A1166C. Therefore, the results indicated that haplotype combinations were not associated with insulin resistance. Key words: insulin resistance, polymorphisms of genes, lipoprotein lipase Ser447Ter (rs328), [beta]2-adrenoreceptor Gln27Glu (rs1042714), angiotensinogenThr174Met (rs4762), angiotensin II receptor type 1 A1166C (rs5186), renin-angiotensin-aldosterone system